Riboflavin modified carbon cloth enhances anaerobic digestion treating food waste in a pilot-scale system - Li, Yiqun; Huang, Yinhui; Li, Haoyong; Gou, Mingyu; Xu, Haiyu; Wu, Hongbin; Sun, Dezhi; Qiu, Bin; Dang, Yan (Frontiers in Bioengineering and Biotechnology, 2024)
Previous laboratory-scale studies have consistently shown that carbon-based conductive materials can notably improve the anaerobic digestion of food waste, typically employing reactors with regular capacity of 1–20 L. Furthermore, incorporating riboflavin-loaded conductive materials can further address the imbalance between fermentation and methanogenesis in anaerobic systems. However, there have been few reports on pilot-scale investigation. In this study, a 10 m2 of riboflavin modified carbon cloth was incorporated into a pilot-scale (2 m3) food waste anaerobic reactor to improve its treatment efficiency. The study found that the addition of riboflavin-loaded carbon cloth can increase the maximum organic loading rate (OLR) by 40% of the pilot-scale reactor, compared to the system using carbon cloth without riboflavin loading, while ensuring efficient operation of the reaction system, effectively alleviating system acidification, sustaining methanogen activity, and increasing daily methane production by 25%. Analysis of the microbial community structure revealed that riboflavin-loaded carbon cloth enriched the methanogenic archaea in the genera of Methanothrix and Methanobacterium, which are capable of extracellular direct interspecies electron transfer (DIET). And metabolic pathway analysis identified the methane production pathway, highly enriched on the reduction of acetic acid and CO2 at riboflavin-loaded carbon cloth sample. The expression levels of genes related to methane production via DIET pathway were also significantly upregulated. These results can provide important guidance for the practical application of food waste anaerobic digestion engineering.